2003
DOI: 10.1148/radiol.2291020561
|View full text |Cite
|
Sign up to set email alerts
|

Multi–Detector Row CT Colonography: Effect of Collimation, Pitch, and Orientation on Polyp Detection in a Human Colectomy Specimen

Abstract: Detection of small polyps (<5 mm) with multi-detector row CT is highly dependent on collimation, pitch, and, to a lesser extent, tube current. Collimation of 1.25 mm, combined with pitch of 6 and tube current of 50 mA, provides for reliable detection of polyps 5 mm or larger while limiting the effective radiation dose. Polyps smaller than 5 mm, however, may be poorly depicted with use of these settings in the transverse colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Their studies focused on finding the imaging effect of collimation, tube current (pitch) and orientation when they analysed different sizes and types of polyps. Similar studies were performed by Taylor et al [49] and Springer et al [50]. Using a different approach, Whithing et al [51] constructed an air filled acrylic cylinder where polyps of different sizes were attached on the 3 inner side of the acrylic tube and they applied the developed phantom to evaluate the artefacts generated by the collimation and the tube current.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Their studies focused on finding the imaging effect of collimation, tube current (pitch) and orientation when they analysed different sizes and types of polyps. Similar studies were performed by Taylor et al [49] and Springer et al [50]. Using a different approach, Whithing et al [51] constructed an air filled acrylic cylinder where polyps of different sizes were attached on the 3 inner side of the acrylic tube and they applied the developed phantom to evaluate the artefacts generated by the collimation and the tube current.…”
Section: Introductionmentioning
confidence: 89%
“…Cohen [43] indicates in his paper that the risk of inducing cancer in patients is significantly lowered when they are subjected to low-level radiation exposure and an important number of studies were carried out in order to identify the minimal level of radiation dose that can be used in CTC but without a negative impact on the detection of colorectal polyps [41,[44][45][46]. The identification of the optimal scanning parameters (collimation, slice thickness, table speed, reconstruction interval) is a difficult problem and this procedure is applied on synthetic phantoms that are designed to accurately model the human body [47][48][49][50][51][52][53][54][55][56][57][58]. In this sense, Beaulieu et al [47] used spherical plastic beads to model polyps while Dachman et al [48] created false polyps in a pig colon by puckering the mucosa of the colon.…”
Section: Introductionmentioning
confidence: 99%
“…A high pitch value decreases the scanning time, a lower tube current reduces the radiation exposure, and a smaller slice thickness improves image quality. A study found that polyps 5-mm or larger in size could be detected with 1.25-mm collimation, pitch of 6, and 60 mA tube current (36). The same study found that the optimal settings for detecting polyps less than 5-mm in size were 1.25-mm collimation, pitch of 3, and 150mA tube current (36).…”
Section: Optimal Settingsmentioning
confidence: 96%
“…A study found that polyps 5-mm or larger in size could be detected with 1.25-mm collimation, pitch of 6, and 60 mA tube current (36). The same study found that the optimal settings for detecting polyps less than 5-mm in size were 1.25-mm collimation, pitch of 3, and 150mA tube current (36). Studies are also being conducted to reduce radiation exposure while still maintaining high sensitivity and specificity values (37).…”
Section: Optimal Settingsmentioning
confidence: 99%
“…MDCT has several technical advantages over single-detector CT, including faster imaging times, reduced exposure to radiation and acquisition of multiple thin sections with nearly isotropic voxels. [2,3,7,11,22,23,[43][44][45][46] Moreover, motion artifacts from respiration and peristalsis are decreased or eliminated with MDCT. [3] Thin sections are a prerequisite for high-quality multiplanar reformations (MPR) and 3D reconstructions.…”
Section: Data Acquisitionmentioning
confidence: 99%